2005
DOI: 10.1007/s11661-005-0284-z
|View full text |Cite
|
Sign up to set email alerts
|

Deformation characteristics of isothermally forged UDIMET 720 nickel-base superalloy

Abstract: The hot deformation behavior of nickel-base superalloy UDIMET 720 in solution-treated conditions, simulating the forging process of the alloy, was studied using hot compression experiments. Specimens were deformed in the temperature range of 1000 °C to 1175 °C with strain rates of 10 Ϫ3 to 1 s Ϫ1 and total strain of 0.8. Below 1100 °C, all specimens showed flow localization as shear band through the diagonal direction, with more severity at higher strain rates. A uniform deformation was observed when testing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(68 citation statements)
references
References 31 publications
5
61
2
Order By: Relevance
“…The average friction coefficient was observed to increase with the increasing strain level. These results did not conform to the conventional viewpoint [8,14] that the friction coefficient as a function of strain level is a constant. There are several reasons existing for the increase in the friction coefficient with an increasing strain level.…”
Section: Resultscontrasting
confidence: 77%
See 3 more Smart Citations
“…The average friction coefficient was observed to increase with the increasing strain level. These results did not conform to the conventional viewpoint [8,14] that the friction coefficient as a function of strain level is a constant. There are several reasons existing for the increase in the friction coefficient with an increasing strain level.…”
Section: Resultscontrasting
confidence: 77%
“…[11,14] In previous research, [8,11,14,15] l was a constant. In this article, l is replaced by the instantaneous friction coefficient obtained from Eq.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The new recrystallized grains nucleate on the deformed grain boundaries and form a necklace around it 7,[11][12][13] , as visible in Figure 5c. It has been reported that during deformation the cooling is slower due to the conversion of deformation energy to heat by adiabatic heating 14 . It is well known that the temperature rise during hot deformation can not only induce the process of DRX, but also lead to a rapid reduction in the work-hardening rate 15 .…”
Section: Microstructurementioning
confidence: 99%